Selected problems of immunotherapy in children - Stańczyk-Przyłuska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
As one of the causal treatment methods in patients with allergic diseases immunotherapy has almost a 100-year history. In spite of such a long period of practice, observation and research in this field, not all relevant problems have been solved. This concerns mainly immunotherapy in treatment of children. Indications for immunotherapy during development age are the same as in maturity. While qualifying for this form of treatment a possibility of allergic disease natural evolution in this age should always be taken into consideration, as well as the greater part of atopy in pathogenesis of asthma in children. Therefore the decision about starting immunotherapy in children should always be preceded by deep and individual assessment. Immunotherapy in children under the age of 5 is not recommended. This is because of the risk of an influence on the developing and growing immune system of a young child. Besides, in young children clinical symptoms often precede development of manifest atopy; therefore these children are also disqualified from this form of treatment. Efficacy of immunotherapy in children is significant. Probably it is a result of greater ability of the growing immune system to modify the immunological response. Preventive influence of immunotherapy in children such as inhibition of illness progress and development of further allergies is also stressed. Frequency of side effects during immunotherapy is similar in all age groups. However, acute systemic reactions happen in children rarely. Sublingual immunotherapy is a case of interest lately. The reduction of clinical symptoms that is gained by using this method is very encouraging. Also the way of application is acceptable to a child and valuable in paediatric practice.